ANALISIS PENERAPAN METODE VARIABLE COSTING DALAM MENENTUKAN HARGA POKOK PRODUKSI PADA UKM DI BANDA ACEH - Sari, Vanda Novita; BZ, Fazli Syam (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
Cost of production is a collection of the costs incurred to process raw materials into finished goods. The study is aimed to know how calculation of the cost of production in the home furnishings industry UKM using variable costing method. the sample of this study as many as 10 SMEs (Annex 3) with Characteristic which produce two-door closet and a dining table laminating a size of 120 x 90 x 75 cm. The method used is descriptive analysis method, which is just to explain or deskriptive how determine Cost of production with ude the Variable Costing of UKM in the industrial sector of building materials for home furnishings in Banda Aceh especially for produce two-door closet and a dining table laminating a size of 120 x 90 x 75 cm. The study states that the calculation of the cost of production is generating significant differences that affect the determination of the selling price. To that end, the company should separate the costs of production and non-production costs and further optimize its production activities so as to produce the exact cost of production at a low cost, order that the company can earn a maximum profit.Keyword: Cost Of Product, Variable Costing.